ELLE of an Opportunity: Student Writers, Civic Audience, and Auction Genre - Sutherland, Robin; Chalmers, William; Currie, Mark (Discourse and Writing/Rédactologie, 2017)
Every February, the Charlottetown chapter of the Canadian Heart & Stroke (H&S) Foundation hosts the “Razzle Dazzle Red” gala, a fundraising event that includes a sit-down dinner and silent and live auctions. “ELLE of an Opportunity” is the name of the very first live auction item, a coordinated jewelry set, listed in the gala program for 2014. Text developed for the jewelry enticed bidders to go big and to go fashionably home: student writer Dani MacDonald invited auction attendees to “hop right onto the trend of big, bold jewelry with this triad from ELLE Canada! The oversized ruby ring adds a note of edginess without compromising sophistication. Pair the ring with matching ELLE ruby earrings and necklace to complete your brave and bold new look!” Who could resist such a high-powered sales pitch?